2019
DOI: 10.11648/j.ijfsb.20190401.11
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Mineral and Sensory Characteristics of Cashew Nut Milk

Abstract: Physicochemical and sensory characteristics of cashew nut milk were investigated. Cashew nut milk was produced and added with sugar and vanilla flavour at different proportions. The proximate and mineral composition of the plain cashew nut milk was analysed, as well as the physicochemical and sensory characteristics of the cashew nut milk containing sugar and vanilla flavour were analysed. The results revealed a reasonable amount of protein (5.00%), fat (5.49%), ash (0.90%) and carbohydrate (5.95%) in the plai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…Pea protein has been found to incorporate off-flavors, including bitterness into the food items (Tarrega et al, 2017), and the ability of the cashew or coconut frozen dessert to mask these flavors may have been the difference between the two samples. The attributes associated with cashew and coconut-based frozen desserts have been found in past studies investigating cashew and coconut-based PBAs (Emelike et al, 2019;Gorman et al, 2023;Grasso et al, 2020;Pachekrepapol et al, 2021;Short et al, 2021) and supports the results of this study.…”
Section: Cashew and Pea Proteinsupporting
confidence: 91%
“…Pea protein has been found to incorporate off-flavors, including bitterness into the food items (Tarrega et al, 2017), and the ability of the cashew or coconut frozen dessert to mask these flavors may have been the difference between the two samples. The attributes associated with cashew and coconut-based frozen desserts have been found in past studies investigating cashew and coconut-based PBAs (Emelike et al, 2019;Gorman et al, 2023;Grasso et al, 2020;Pachekrepapol et al, 2021;Short et al, 2021) and supports the results of this study.…”
Section: Cashew and Pea Proteinsupporting
confidence: 91%
“…Formulations with higher proportions of cashew nuts (6%) and prunes (12%), such as F4, had lower moisture values, whereas formulations containing smaller proportions of cashew nuts (3%) and prunes (9%), such as F1, had higher moisture values. Similar moisture results were found for cashew nut milk (Tamuno & Monday, 2019). The ash values found in the formulations showed no differences, and were similar to those of plant-based beverages prepared with rice, sesame, or almond (Aydar et al, 2020).…”
Section: Physicochemical Characterization Of Raw Materials and Vegetal Beveragessupporting
confidence: 78%
“…The obtained results for the proximate analysis of all milk samples are presented in Table 2. The moisture content of the cashew milk and soy milk beverage were 64.22% and 62.40%which are lower than the value of 82.66% reported by Emelike et al [17] for cashew milk. Also, Muhammad et al [18] reported moisture content of 87.12% for cashew milk and 88.12% milk for soy milk.…”
Section: Table 1: Chemical Composition Of Cashew Kernelcontrasting
confidence: 66%
“…Table 3 above shows the result of mineral and vitamins analysis performed on cashew nut milk, it contains 52.5 mg/100 g of calcium, 53.2 mg/100 g of phosphorus while the iron content was 5.2 mg/100 g. Values obtained for calcium and phosphorus were higher than 4.75 mg/100 g and 2.00 mg/100 g reported by Emelike et al [17]. Also, the iron content in this report was higher than the results of Muhammad et al [18], who reported a value of 0.8 mg/100 g for iron.…”
Section: Results Are Mean Values Of Duplicate Determinationsmentioning
confidence: 78%